Konstruksi Agama dan Masyarakat Atas Tubuh (Studi Kasus Penari Lengger Desa Gerduren Kecamatan Purwojati Kabupaten Banyumas) - Robertus Suraji (Media Aplikom, 2012)
A person’s body is the most essential of the person’s belonging. However, the body itself is not only one’s private belonging, but it has become a sign system of a culture in a certain society. Not only does the body have specific meaning for himself, but it also has social and even transcendental dimension. For Indonesians, Ethics-related to human bodies nowadays seems to be the highest hierarchy of public morality. One’s body is often accused to be the cause of moral destruction of the nation’s later generation. As a further result, people feel uncertain, even anxious to explore their own body because they ultimately have to deal with the groups who have opposing views. Legger dance as an art that explores the dancer’s body often has to deal with the moral judgments of the society, especially the religious believer groups. The existence of Lengger dance as a traditional art is highly depended on the views of its supporting groups about one’s body. Meanwhile, the construction of public views on one’s body to support Lengger dance is intensively affected by those who have authority to make public opinion about one’ body. Those who have the authority will define and control one’s body in the society and decide the meaning of it according to their point of view and interests. Therefore, one’s body can be personal body that can be trained for the sake of religion, politics and economics. One’s body can enter into negotiation and conflictive battlefield. On the other hand, it does not mean that the discourse about one’s body only has mono- interpretation. It is a fact that art and culture has its own specific autonomy. The Lengger dancers have their point of view about one’s body, and they greatly give specific meaning about one’s body in relation to other persons and to the transcendence. And so, it is important to write down one’s personal experience in the study about one’s body in the Lengger dance. Dealing with the transcendence, Lengger dancers take captive the divine aspects in their own body language. They believe that one’s body is the creation of God, so the hand of the Creator can easily be found in one’s body. This believe becomes a challenge for Lengger artists how to make their own body movement help other persons come to God. The Lengger dancers need to transform their own body, so the body language can make people know one’s body better, and then it comes to recognize God, the Creator, through their body language, instead of thinking about eroticism that makes people lose their mind to believe in God in their own inner body. In addition, it is also important to establish the new meanings and discourses continuously, then there must be a hard attempt to renew the Lengger dance style, so the dance style of Lengger matches to the new meaning and discourse.